Nation-Wide Dissemination of a Digital Checklist to Improve Work Environment in the Eldercare Sector in Denmark - Munch, Pernille Kold; Jørgensen, Marie Birk; Højberg, Helene; Rasmussen, Charlotte Diana Nørregaard (Frontiers in Public Health, 2020)
In this study, we evaluated the dissemination of a digital checklist for improving implementation of work environment initiatives in the Danish eldercare sector. We evaluated the impact of the checklist using the RE-AIM framework. Initiated in 2016, researchers and relevant stakeholders were responsible for disseminating the checklist to all workplaces in the eldercare sector in Denmark through a national campaign. The checklist guided the user to define an action plan to implement, and the checklist covered 11 implementation concept points that should be addressed to reach full implementation of the action in focus. One year after the launch of the campaign almost all municipalities in Denmark had visited the website hosting the checklist (96%), 17% of individual workers within the eldercare responding to a union survey was reached, 4% (n = 199) of all eligible eldercare workplaces in Denmark and 8% of all nursing homes had adopted the checklist. Of the workplaces that used the checklist, 46% typed an action in the checklist. There were 13% of the first time users that used the checklist twice and 29% of the actions were revised (maintenance) after working with the implementation. Finally, the workplaces that had used the checklist showed a higher prioritization of work environment compared to workplaces not using the checklist both at baseline and at follow up. In conclusion, this study employing various strategies, including a 1-year national campaign to disseminate a checklist shows potential to impact implementation of work environment initiatives in the Danish eldercare sector. While dissemination is satisfactory and likely to increase further with time, more efforts is needed to ensure maintenance.